2018
DOI: 10.1371/journal.pone.0193451
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid rich Ocimum sanctum L leaf extract loaded nanostructured lipid carriers ameliorate adjuvant induced arthritis in rats by inhibition of COX-1, COX-2, TNF-α and IL-1: Pharmacological and docking studies

Abstract: BackgroundUrsolic acid (UA) is a promising molecule with anti-inflammatory, analgesic and potential anti-arthritic activity.MethodsThis study was undertaken to make formulation and evaluation of Ocimum sanctum L. leaf extract (OLE) loaded nano-structured lipid carriers (OLE-NLCs) for improved transdermal delivery of UA. Different surfactants, solid lipids and liquid lipids were used for the preparation of NLCs. The NLCs were developed using emulsion solvent diffusion and evaporation method. Different physicoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 43 publications
(44 reference statements)
0
28
0
Order By: Relevance
“…Pharmacokinetic study revealed that elimination rate constant of intravenous lansoprazole solution was higher than NLC hydrogel indicating prolonged plasma residence and hence extended inhibition of gastric acid secretion. Recently, Ocimum sanctum L. leaf extract (rich in ursolic acid) loaded NLCs were prepared and evaluated for anti-inflammatory effect after topical application ( Ahmad et al 2018 ). NLCs showed excellent anti-arthritic activity when compared to standard marketed diclofenac gel.…”
Section: Applications Of Nlcsmentioning
confidence: 99%
“…Pharmacokinetic study revealed that elimination rate constant of intravenous lansoprazole solution was higher than NLC hydrogel indicating prolonged plasma residence and hence extended inhibition of gastric acid secretion. Recently, Ocimum sanctum L. leaf extract (rich in ursolic acid) loaded NLCs were prepared and evaluated for anti-inflammatory effect after topical application ( Ahmad et al 2018 ). NLCs showed excellent anti-arthritic activity when compared to standard marketed diclofenac gel.…”
Section: Applications Of Nlcsmentioning
confidence: 99%
“…Terpenoids of plant extracts have potent anti‐inflammatory activity (Prakash, 2017). Moreover, studies have suggested that ursolic acid (UA) is used as a promising molecule with anti‐inflammatory, analgesic, and potential anti‐arthritic activity and diabetes (Ahmad et al., 2018; Bacanlı, 2020). Ursolic acid, found in Citrus plants, is one of the important natural pentacyclic triterpenoid carboxylic acids (Ahmad et al., 2018; Mahlo & Eloff, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Solid lipid nanoparticles (SLNs) are the most promising oral drug delivery carriers due to their long term stability, high drug-loading capacity, excellent biocompatibility, largescale production viability and long-term stability. Furthermore, previous researcher suggests that the SLN increased the intracellular drug delivery for anti-arthritic drugs (Arora et al, 2015;Ahmad et al, 2018). SLNs are a colloidal system primarily formulated of solid lipids.…”
Section: Introductionmentioning
confidence: 99%